Preparation and induction for school principals: global perspectives - Bush, Tony (Sage, 2018)
This article will examine different international approaches to leadership preparation and induction, linked to concepts of socialization and identity. Although leadership is widely understood to be the second most important factor influencing student outcomes, principal preparation is neglected in many countries. A teaching qualification and teaching experience are often considered to be sufficient attributes for new principals. The article will argue that being a principal is a different role from classroom teaching and requires specific preparation. This involves three phases of socialization. First, aspiring leaders require professional socialization, preparing to become a principal. Second, they need to change their identity, from teacher to principal. Third, they need a period of organizational socialization, learning to lead in a specific school. The article will draw on international research and literature to consider the experience of new principals in different settings. It will also examine examples of preparation and induction in several settings to establish what works effectively and in what contexts. It will also consider the role of mentoring in successful principal preparation and induction, bearing mind the need for induction to be an extended process, not a 'one-off' event. The article will conclude with a model for leadership preparation and induction, which could be applied in many places, subject to careful adaptation to fit the local culture and context.